The Impact of EPS, PER, CR, and ROE on the Sharia Share Prices on the Indonesia Stock Exchange - Umardilopa, Jevi Azi; Projo, Nucke Widowati Kusumo (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2025)
The public's demand for Sharia-compliant investment has been increasing in tandem with the growth of the Muslim populations. Between 2019 and 2023, the total number of Sharia-compliant stock firms listed on the Indonesia Stock Exchange (IDX) has consistently remained stable or increased, with no recorded decline. Despite this promising trend, Sharia companies show quite volatile stock price movements. Therefore, conducting a financial ratio analysis is essential. Financial ratios such as Earnings per Share (EPS), Price to Earnings Ratio (PER), Current Ratio (CR), and Return on Equity (ROE) are useful for assessing a company's valuation. This study's novelty lies in integrating Sharia principles with financial ratio analysis to evaluate the financial health of Sharia-compliant firms. This research aims to analyze the influence of EPS, PER, CR, and ROE on the stock prices of Sharia companies. The research utilizes secondary data from the second trimester of 2023, obtained from the IDX. The research employs descriptive and inferential analysis using robust regression. The findings indicate that EPS variable, PER variable, and ROE variable have a positive and significant impact on Sharia stock prices. Conversely, CR has no significant effect and has a negative correlation with the stock prices of Sharia companies. Therefore, investors need to consider the EPS value, PER, and ROE before making investment decisions.